Community health systems and priority setting for elderly healthcare services in rural Tanzania: Experience from Nzega and Igunga districts - Malale Tungu; Nathanael Sirili; Amani Anaeli; Gasto Frumence (PLoS ONE, 2025)
Introduction In the 1990s, Tanzania adopted health sector reforms with the aim of engaging the local communities in priority setting and decision-making for effective and efficient use of resources. Community engagement aims to enhance community voice and efficiently allocate available resources according to the citizen’s demands to achieve the targeted health outcomes. The Community Health Systems (CHS) aim to strengthen Primary Health Care (PHC) services by empowering all community actors close to and serving community members. This study explored the role of the CHS during priority setting process in improving health services for the elderly in rural Tanzania. Methods An exploratory case study design was employed to collect data using Key Informants Interviews (KIIs) in Nzega and Igunga districts. Purposeful sampling was used to select participants from the two districts. Twenty-four (12 from each district) interviews were conducted with community representative members of the Health Facility Governing Committee (HFGC), social welfare, Council Health Management Team (CHMT), District medical officers, Medical Officers in-charge (MOI), planning officers and health system information focal person. All audio recorded interviews were transcribed verbatim. The transcribed interviews were translated from Kiswahili to English. The data were analyzed using the content analysis approach. The transcribed data, field notes, and documents were reviewed and read to identify broad areas in which to form initial codes and codes. Similar codes with related concepts were grouped to form initial categories and categories. Results The findings of this study demonstrated the importance of CHS in strengthening community participation in identifying the elderly who are in need in the community and been involved in elderly matters during priority setting of the elderly health services through the health facility governing committee. This means that there was community participation in elderly matters especially to help the elderly reach health facilities and during priority setting, positive and negative perceptions among community members about the elderly agenda during priority setting. In addition, the findings show that there is poor awareness among community members including family members who perceive that the government is responsible for providing health services to the elderly and not the community or family members. Conclusion The findings of this study indicate the importance of community during the priority setting process which plays a great role in identifying the elderly who are in need and the most needed health services for the elderly in their communities. Therefore, the Local government authority should fully involve CHWs in collaboration with all community actors to address elderly matters in rural areas and improve elderly healthcare services. The community members have to be educated and raise awareness about elderly health matters through different platforms such as during world elderly day, village meetings and at the health facility level.